Uji Aktivitas Antibakteri Ekstrak Daun Cengkeh (Syzygium aromaticum L.) Terhadap Bakteri Staphylococcus epidermidis : Uji Aktivitas Antibakteri Ekstrak Daun Cengkeh (Syzygium aromaticum L.) Terhadap Bakteri Staphylococcus epidermidis - Nurhayatina, Rina; Hadiwijaya, Muhammad Reynaldi; Sukmawati (LP4M STIKes Karsa Husada Garut, 2025)
Introduction: Staphylococcus epidermidis is one of the bacteria that causes acne on the skin and can cause opportunistic infections against weak immunity. Method: This method uses cold liquid extraction with maceration technique with 96% ethanol solvent and disc diffusion to determine the activity against bacteria by using distilled water as a negative control and amoxicillin as a positive control. Result: shows inhibitory power at concentrations of 25%, 50% and 75% with inhibition zones of 9.3 mm, 9.16 mm, 7.83 mm. Conclusion. The effective concentration to inhibit the growth of Staphylococcus epidermidis bacteria is 25%, namely 9.3 mm, which is included in the medium category. Keywords: Antibacterial, clove leaf, Staphylococcus epidermidis, thick extract